Pengaruh Pengendalian Internal dan Independensi Auditor terhadap Pencegahan Kecurangan (Fraud) pada Kantor Akuntan Publik di Jakarta Selatan - Prima Dolorosa Seran; Sairun Simanullang; Desyi Erawati (International Forum of Researchers and Lecturers, 2024)
This study aims to determine the magnitude of the influence of Internal Control and Auditor Independence on Fraud Prevention at Public Accounting Firms in South Jakarta. This study uses a quantitative research method. The data source used is primary data. Data collection techniques in the form of questionnaires. The sample collection method in this study is non-probability sampling. There are 70 respondents consisting of 9 public accounting firms in South Jakarta. The results of the study show that the calculated t value is greater than the t table value of 3.778> 1.667, meaning that Ho is rejected and Ha is accepted. This means that the Internal Control variable (X1) significantly influences Fraud Prevention (Y). Based on the calculated t value greater than the t table value (4.126> 1.667), meaning that Ho is rejected and Ha is accepted. This means that the Auditor Independence variable (X2) significantly influences Fraud Prevention (Y). From the calculation results with SPSS 25.0, it was found that the coefficient of determination (Adjusted R Square) was 0.723. This indicates that the Internal Control Variable Auditor Independence Variable affects the Fraud Prevention Variable by 72.3% and the remaining 27.7% is explained by other factors (other variables) that were not examined in this study.